Relationship between Policy and Practices of Decision Making in Public Schools (Interdisciplinary Research in Education, 2021)
This study is critically analyzed the relationship between policy and practices of decision making in public schools of Nepal. I tried to explore the relationship between policy and practicesin two districts of Kathmandu valley by using qualitative data using power and decentralization theoryand different decision-making models.  I understood that parents, head teacher, and teachers apply decentralization cum power theory in decision making practices in schools. I also found that these authorities mainly take decisions in physical resource management, teacher recruitment, and program extension.  I also came to understand that mixed- model approach is blended between head teacher, teacher and community control model. At the practicing level, I found gap in the use of power in various aspects of decision making.  I also found that these gaps were observed because of practicing of head teacher control model. The study implies that decision making process at the school level needs a new model that must be more contextual and participatory for the effective school management.